Bahasa dan Pembentukan Citra dalam Komunikasi Periklanan di Televisi - Anwar Efendi (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2008)
Language in an advertisement has two functions. The first is language as a means of communication and thesecond is language as a means of forming social reality. The first function deals with its use as a source of information, whilethe second deals with its use as a creative art in engineering expected world or condition. As a source of information, thelanguage becomes a means of delivering true information about a certain product being advertised to people. It describesall the details of the product, such as the use, advantages, and ease. This is intended to make consumers know well aboutthe product and decide t buy it. As a means of forming social reality, the language in advertisement is used to create animage about the product for the consumers. This process of building image represents in making association between theproduct and life style, social class, and symbols of modernity.